SunBay Digital Mathematics: A Scalable Collaboration - Fueyo, Vivian; Roy, George; Vahey, Phillip (Educational (Re)naissance, 2013)
By leveraging the strengths and commitments of each of the partners, a university, a private nonprofit, and a middle-sized urban school district, collaborated to impact student learning of key concepts in middle-grade mathematics and to change mathematics teaching. The project targeted middle grades mathematics because success in it is the greatest predictor of later school achievement. In well-researched learning modules, students visualize, interact with, and analyze mathematical representations connected to dynamic simulations of real-life phenomena in a curricular learning system comprising dynamic technologies, curriculum replacement units, and professional development. Through planned professional development, teachers have the technological skills, pedagogical skills and mathematical content knowledge required to engage their students in an interaction between the software, the curriculum materials, and the mathematics. Student learning gains and changes in teacher pedagogical, technological, and mathematical content knowledge provide evidence of the project’s continued success after three years. Concomitant institutional changes in each of the partnering organizations attest to the project’s sustainable impact.